Measuring Joint Hypermobility Using the Beighton Scale in Children With Intellectual Disability. Issue 2 (2015) - Pitetti, Ken; Miller, Ruth Ann; Beets, Michael W.
Abstract : Purpose: To determine the feasibility and reliability of using the 9-point Beighton Hypermobility Score (9-BHS) with youth with intellectual disabilities using a least to most prompting technique. Method: One hundred one youth (5-18 years old) enrolled in the study. Two separate evaluations, separated by 3 to 4 weeks, were performed on 25 participants. Results: Ninety assented to the test, and 85 performed all 9-BHS maneuvers. Scores were not significantly different for age and gender, but participants with Down syndrome had significantly higher scores. Test-retest scores showed 80% to 90% agreement (n = 25). Cohen kappa ranged from moderate (0.41-0.60) to perfect (1.0) for the 9 maneuvers, and an ICC of 0.88 was found for total scores. Conclusion: The results demonstrate that the use of the 9-BHS in youth with intellectual disabilities in the manner described is feasible and reliable. Abstract : The authors demonstrate the feasibility and reliability of using the Beighton Scale in children with intellectual disability.